ALCOHOLIC CARDIOMYOPATHY: BASIC ASPECTS OF EPIDEMIOLOGY, PATHOGENESIS AND PHARMACOTHERAPY - A. O. Yusupova (Столичная издательская компания, 2015)
Data on the epidemiology and pathogenesis of alcoholic cardiomyopathy (ACMP) are presented. Special aspects of clinical manifestations as well as management of these patients are considered. Psychotropic therapy aimed at reduction in motivation to alcohol consumption in patients with ACMP is discussed separately.